Pengaruh kredibilitas pustakawan terhadap kepuasan pemustaka di Perpustakaan Universitas Amikom Purwokerto - Prayoga Pribadi; Dwininda Kusumawardhani (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. The credibility of librarians is one of the factors that support user satisfaction with library services. This study discusses the impact of the expertise, attractiveness and trustworthiness of librarians on the user satisfaction at the Amikom University Library, Purwokerto. Data Collection Methods. This study uses a quantitative approach, quota method, with a total sample of 188 people. Data Analysis. The data were tested using validity, reliability, multiple regression, and hypothesis test involving t-test and f-test. Results and Discussion. H0 was rejected and H1 was accepted. It can be seen that the credibility of librarians affects the user satisfaction by 31.7% and another 70% was influenced by other things that were not examined in this study. Based on data analysis, the results showed that authenticity, trustworthiness, and attractiveness have significant impacts on user satisfaction. Conclusion. Although several aspects are considered as supporting factors, a credible librarian supports user satisfaction significantly.